Penerapan Model Pembelajaran (CTL) pada Pembelajaran Puisi Siswa Kelas IV Madrasah Ibtidaiyah - Tsalitsatul Maulidah; Samrotul Islamah (IBTIDA', 2020)
Learning literature is an integral part of the educational environment. One of the innovative lessons that help students understand the material and improve their thinking skills in poetry material is learning using the Contextual Teaching and Learning (CTL) learning model. This type of research is an experimental research. In this study, researchers designed their research using a one group pretest-postest design. The characteristic of this design is that there is a pretest before being given treatment and posttest after being given the treatment, so that the results obtained are that the percentage is 100%. With this percentage it can be stated that the textbook based on the CTL learning model is very good.